Forefront of Na+/Ca2+ Exchanger Studies: Stoichiometry of Cardiac Na+/Ca2+ Exchanger; 3:1 or 4:1? - Masamitsu Hinata; Junko Kimura (Journal of Pharmacological Sciences, 2004)
The stoichiometry of the Na+/Ca2+ exchanger (NCX) had been generally accepted as 3Na+:1 Ca2+. However, recently a challenging stoichiometry of 4:1 was proposed. Therefore, using guinea pig ventricular cells, we re-examined the stoichiometry by measuring the reversal potential of the NCX current and intracellular Ca2+ concentrations under the whole-cell voltage clamp. We confirmed that the stoichiometry of NCX is 3:1 not 4:1. In addition, we explored the possible reasons for obtaining erroneous results of a 4:1 stoichiometry. Keywords:: Na+/Ca2+ exchanger (NCX), stoichiometry, cardiac myocyte